(untitled) (Eurasian Research Bulletin, 2021)
The article considers the pilgrimage terms in the English language. Pilgrimage tourism is a kind of religious tourism and is a combination of trips of representatives of various religions for pilgrimage purposes. We consider pilgrimage as a journey of people to worship holy places. The article highlights various types of pilgrimage but emphasized Bukhara’s holy sites for pilgrimage tourism and its peculiarities